HUBUNGAN PERAN BIDAN DAN DUKUNGAN SUAMI DENGAN KEPATUHAN IMUNISASI TT PADA PRIMIGRAVIDA - Lenni Sello; Adriana Mangalla (KOLONI, 2022)
The implementation of TT immunization activities for pregnant women consists of routine immunization activities and additional activities. Routine immunization activities are immunization activities that routinely and continuously must be carried out at a predetermined time period, the implementation of which is carried out inside buildings (static components) such as health centers, sub-health centers, hospitals, maternity homes and outside buildings such as posyandu or through home visits. Additional immunization activities are immunization activities carried out on the basis of finding problems from the results of monitoring or evaluation. The purpose of this study was to determine the relationship between the role of midwives and husband's support with TT immunization compliance in primigravida at Puskesmas Kondoran, Tana Toraja Regency. The study was conducted in November 2021. The population in this study were all primigravida pregnant women who came to visit the Kondoran Health Center, Tana Toraja Regency as many as 30 people. In this study, the sample taken was primigravida pregnant women who came to visit the Kondoran Health Center, Tana Toraja Regency with total sampling, namely taking respondents by taking all the population as a sample of 30 people. The results showed that there was a relationship between the role of midwives and adherence to TT immunization of primigravida mothers with p value = 0.001. The results showed that there was a relationship between husband's support and adherence to TT immunization of primigravida mothers with p value = 0.005. It is hoped that health workers, especially midwives, will provide information through counseling about tetanus toxoid (TT) immunization. Keywords: Role of Midwife, Husband Support, Immunization Compliance